HUBUNGAN PERHATIAN ORANG TUA DENGAN KEMATANGAN KARIR SISWA SMK SWASTA AL-MAKSUM STABAT - Azri Ranuwaldy Sugma (LPPM STKIP AL MAKSUM, 2019)
This study is aimed to knowing the correlation between parental attention with students’ career maturity SMK Swasta Al-Maksum Stabat. The hypothesis that submitted was, there is positive correlation between parental attention with students’ career maturity with assuming that the higher parental attention the higher career maturity. Where the sample of this study was the students of class X and XI SMK Swasta Al-Maksum Stabat with the population were 422 students and the sample were 105 students that got by using proportional random sampling technique. The data collection was did by using Likert Scale that includes of two scales, there are scale parental attention and career maturity scale. The data analysis method that used was Multiple Regression Analysis. From result of data analysis found that there is a significance of positive correlation between parental attention with career maturity students’ of SMK Swasta Al-Maksum Stabat, that is shown by coefficient F= 59,299 and P < 0,05.Parental attention gives the contribute to career maturity as much as 54,5%.